Pengaruh Pendidikan Agama Islam Terhadap Pembentukan Karakter Peserta Didik di Sekolah Dasar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Character development is a crucial element in the educational landscape, particularly in elementary schools where a child's personality starts to take shape. An effective approach to cultivating students' character is through Islamic Religious Education (PAI). This research seeks to evaluate how significantly Islamic Religious Education impacts the character development of elementary school students. A qualitative method is employed for this investigation, utilizing observation methods, interviews, and documentation concerning PAI teachers and students from various elementary schools. The findings from the research show that Islamic Religious Education plays a crucial role in promoting character traits like integrity, self-control, accountability, and acceptance. Effective learning, teacher role models, and religious activities in schools are supporting factors for the success of character education. On the other hand, limited lesson time and lack of parental involvement are challenges in its implementation. In conclusion, Islamic Religious Education has an important role in forming the character of students holistically from an early age.